Measurement of the photodissociation of the deuteron at energies relevant to Big Bang nucleosynthesis. Issue 1 (January 2016) - Hannaske, R; Bemmerer, D; Beyer, R; Birgersson, E; Ferrari, A; Grosse, E; Junghans, A R; Kempe, M; Kögler, T; Kosev, K; Marta, M; Massarczyk, R; et al.
Abstract: The photodissociation of the deuteron is a key reaction in Big Bang nucleosynthesis, but is only sparsely measured in the relevant energy range. To determine the cross section of the d(γ, n)p reaction we used pulsed bremsstrahlung and measured the time-of-flight of the neutrons. In this article, we describe how the efficiency of the neutron detectors was experimentally determined and how the modification of the neutron spectrum by parts of the experimental setup was simulated and corrected.